2010
DOI: 10.1111/j.1476-5381.2010.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Valerenic acid derivatives as novel subunit‐selective GABAA receptor ligands –in vitro and in vivo characterization

Abstract: BACKGROUND AND PURPOSE Subunit‐specific modulators of γ‐aminobutyric acid (GABA) type A (GABAA) receptors can help to assess the physiological function of receptors with different subunit composition and also provide the basis for the development of new drugs. Valerenic acid (VA) was recently identified as a β2/3 subunit‐specific modulator of GABAA receptors with anxiolytic potential. The aim of the present study was to generate VA derivatives as novel GABAA receptor modulators and to gain insight into the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…In contrast, NE system modulators enhance ICF [30]. These mechanisms are remarkably consistent with the premise that VE, and, particularly valerenic acid, the main component of VE, allosterically modulate GABA A receptors and, in this way, are thought to induce anxiolytic activity [31,32,33,34]. A similar modulatory effect on the GABA A channel was demonstrated for other components of the VE such as alerenol, 6-methylapigenin, and linarin [35,36].…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, NE system modulators enhance ICF [30]. These mechanisms are remarkably consistent with the premise that VE, and, particularly valerenic acid, the main component of VE, allosterically modulate GABA A receptors and, in this way, are thought to induce anxiolytic activity [31,32,33,34]. A similar modulatory effect on the GABA A channel was demonstrated for other components of the VE such as alerenol, 6-methylapigenin, and linarin [35,36].…”
Section: Discussionsupporting
confidence: 57%
“…To show that this is a specific effect, we also co-applied these compounds with modulatory ligands that do not elicit modulation via the a+/b-site (Ramerstorfer et al, 2011). As expected, the GABA potentiating effects of ROD 188 (Thomet et al, 2000; Figure 3B) or of valerenic acid amide (Khom et al, 2010; data not shown) remained unaltered in the presence of compounds 23, 25, 27 or 33. These data indicated that these compounds were able to specifically block the effects of compound 11 mediated via the a1+b3-binding site without interfering with the action of compounds binding to an unrelated binding site of a1b3 receptors.…”
Section: Some Compounds Are Null Modulators At the A1+b3-binding Sitementioning
confidence: 99%
“…Valerenic acid from Valeriana officinalis roots is a β 2/3 -subunit-specific positive allosteric modulator 44,48 with anxiolytic effects in vivo. 48,49 This compound has served as a new scaffold for GABA A receptor ligands. 49,50 Among the compounds identified by the profiling of Acorus extract, the simple phenylpropanoid β-asarone (1) induced the highest potentiation of I GABA (1200% ± 163% with an EC 50 of 171.5 ± 34.6 μM).…”
Section: Resultsmentioning
confidence: 99%
“…48,49 This compound has served as a new scaffold for GABA A receptor ligands. 49,50 Among the compounds identified by the profiling of Acorus extract, the simple phenylpropanoid β-asarone (1) induced the highest potentiation of I GABA (1200% ± 163% with an EC 50 of 171.5 ± 34.6 μM). Its efficiency at a GABA EC 5-10 was significantly Zaugg et al Page 4 higher than that of known GABA A receptor modulators such as benzodiazepines (triazolam: 253% ± 12%, midazolam: 342% ± 64%, clotiazepam: 260% ± 27%) 51 or natural products such as valerenic acid (400% ± 78%).…”
Section: Resultsmentioning
confidence: 99%